Substituent effects on the stretching vibration of C═N in multi‐substituted benzylideneanilines. (20th May 2019) - Wang, Linyan; Cao, Chaotun; Cao, Chenzhong
Abstract: Forty‐nine samples of 3, 4′/4, 3′/3, 3′‐disubstituted benzylideneanilines (XBAYs) and 52 samples of multi‐substituted XBAYs were synthesized, and their infrared absorption spectra were recorded in this paper. On the basis of the stretching vibration frequencies νC═N of C═N bridging bond of 158 samples of substituted XBAYs (including 57 samples of 4, 4′‐disubstituted XBAYs from reference and 101 samples of substituted XBAYs synthesized in this paper), an extensional research of substituent effects on the νC═N values from 4, 4′‐disubstituted XBAYs to multi‐substituted XBAYs was made. A modified equation for quantifying the νC═N values of multi‐substituted XBAYs was obtained (shown as Equation (3)). Equation (3) indicates that the excited‐state substituent constant of Y and the substituent specific cross‐interaction effect between X and X cannot be ignored for the quantitative regression analysis of the νC═N values of multi‐substituted XBAYs. Compared with Equation (1), Equation (3) has a wider application and more accuracy in quantifying the νC═N values of substituted XBAYs. Abstract : An extensional research of substituent effects on the νC═N values from 4, 4'‐disubstituted XBAYs to multi‐substituted XBAYs was made in this paper. And a modified equation quantifying the νC═N values of multi‐substituted XBAYs was obtained (shown as Equation 3). The results show that the excited‐state substituent constant of Y and the substituent specific cross‐interaction effect between X and X cannot be ignored for the quantitative regression analysis of the νC═N values of multi‐substituted XBAYs.